2014
DOI: 10.1007/978-3-319-13386-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Human Classification Using Gait Features

Abstract: Abstract. Gait exhibits several advantages with respect to other biometrics features: acquisition can be performed through cheap technology, at a distance and without people collaboration. In this paper we perform gait analysis using skeletal data provided by the Microsoft Kinect sensor. We defined a rich set of physical and behavioral features aiming at identifying the more relevant parameters for gait description. Using SVM we showed that a limited set of behavioral features related to the movements of head,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…In our implementation we repeat the same steps on both right and left strides. Stride detection is based on the ankles joints whose estimated positions turn to be stabler than the feet joints (see our previous analysis in [16,17]). …”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our implementation we repeat the same steps on both right and left strides. Stride detection is based on the ankles joints whose estimated positions turn to be stabler than the feet joints (see our previous analysis in [16,17]). …”
Section: Proposed Methodsmentioning
confidence: 99%
“…In [16,17] it is shown that gait features extracted from Kinect can be used as a biometric signature. Gabel et al [18] have performed full body gait analysis for continuous gait monitoring at home.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, in order to reduce the computational cost as well as to acquire accurate model fitting, many researches related to algorithms for modeling and tracking body part, such as primitive shapes and stick figures have been carried out [7], [8], [18]- [23]. However, recent researches attempt to overcome the drawbacks by applying a new generation of image acquisition device, known as Kinect Sensors for human gait recognition purpose [24]- [29]. Compared to a standard video camera, Kinect generates model fitting of stick-figure model accurately and further tracks human without involving complex processes for distance between 0.8 m to 4 m [30].…”
Section: B Human Gait Recognition With Kinectmentioning
confidence: 99%
“…Researchers developed feature extraction technique that involved both static and dynamic features. As a result, high recognition performance were obtained based on findings reported based on static features [27], [30]- [33] as well as fusion of static and dynamic features [26], [28], [29], [34], [35]. The worst recognition performance reported using dynamic features were findings from [26], [27], [36], [37].…”
Section: B Human Gait Recognition With Kinectmentioning
confidence: 99%
“…In the work (Gianaria et al, 2014), gait analysis is performed using skeletal data provided by Microsoft Kinect sensors and a set of physical and behavioural features is defined, in order to identify the more relevant parameters for gait description. The aim of this work is the gait characterization and people recognition using SVM classification.…”
Section: Related Workmentioning
confidence: 99%